2020
DOI: 10.1111/acer.14501
|View full text |Cite
|
Sign up to set email alerts
|

Binge‐Like Exposure During Adolescence Induces Detrimental Effects in Alveolar Bone that Persist in Adulthood

Abstract: Background Alcohol (EtOH) intake during adolescence has become an important public health issue. Although the detrimental effects of EtOH intake on the musculoskeletal system are well known, only a few studies have investigated its impact on the stomatognathic system of adolescents. This study aimed to investigate the effect of EtOH binge drinking on the alveolar bone and the long‐term consequences after abstinence. Methods Adolescent female Wistar rats (35 days old) were exposed to 4 cycles of EtOH binge drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Concurrently, systemic influences encompass variables such as sex hormone levels and nutritional status, further underscoring the multifaceted nature of alveolar bone dynamics [ 9 ]. The interaction between bone and immune cells as modulator factors in physiological bone modeling and remodeling helps preserve mineral homeostasis [ 27 , 28 ]. Due to its distinct features, the alveolar bone differs from other bones and is specifically designed to support tooth activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, systemic influences encompass variables such as sex hormone levels and nutritional status, further underscoring the multifaceted nature of alveolar bone dynamics [ 9 ]. The interaction between bone and immune cells as modulator factors in physiological bone modeling and remodeling helps preserve mineral homeostasis [ 27 , 28 ]. Due to its distinct features, the alveolar bone differs from other bones and is specifically designed to support tooth activity.…”
Section: Discussionmentioning
confidence: 99%
“…Made of compact bone with thick trabeculae and fewer, closer trabeculae than other bones, it indicates high bone mass and mineralization [ 29 ]. The alveolar bone also has a unique adaptive response to stimuli, a result of its high bone mass and mineralization, which distinguishes it from other bones [ 28 ]. Given the significance and unique traits of the alveolar bone, we chose to examine the impact of açai supplementation on it.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study are in line with previous research that utilized microtomographic evaluation and demonstrated a reduction in bone volume fraction, bone density and trabecular thickness in rats with ligature‐induced periodontitis exposed to alcohol (Frazão et al., 2020) and nicotine (Liu et al., 2010) consumption. Additionally, one study reported that alcohol consumption led to a decrease in alveolar bone density, a reduction in trabecular thickness and an increase in trabecular separation in rats, even in the absence of periodontitis induction (Maia et al., 2021). Another study also showed that chronic alcohol consumption decreased bone density in the periapical region of rats submitted to apical periodontitis, assessed by digital radiographs (Dal‐Fabbro, Marques de Almeida, Cosme‐Silva, Neto, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Following binge-drinking cycles administration, both ethanol and control groups were subdivided in 3 periods of withdrawal assessment, i.e., 1 (59 th days old), 30 (88 th days old), and 60 (118 th days old) days [31]. The withdrawal periods were chosen to assess the early, mid, and late adulthood perspective [32][33][34][35].…”
Section: Ethanol Binge-drinking Protocol and Experimentalmentioning
confidence: 99%